Islamic operations management: theories and applications - Islam, Rafikul (Routledge, Taylor & Francis Group, 2024)
Managing operations is an integral part of all business and comprises a number of components, including quality management, production planning, supply chain management, logistics, and inventory control. The effective management of operations plays a defining role in enhancing business efficiency and is a lynchpin for success.